“Comportamiento agronómico del Cultivo de Arroz (Oryza Sativa.)a la aplicación de programas combinados de fertilización química y materia orgánica, en Babahoyo,Los Ríos” - Aviles Contreras, Omar Manuel (2019)
SUMMARY The present experimental work was carried out in the premises of the "CEDEGE" project belonging to the Technical University of Babahoyo, it is located at Km 10,5 of the Babahoyo - Montalvo road. Eight treatments and three repetitions were investigated. The objective of the research was the application of chemical fertilizers plus the application of organic fertilizers in the production of rice. Rice sowing was carried out with the SFL-11 variety in experimental units of 10 m2. The treatments were distributed in a split plot design. The evaluation of means was made with the Tukey test at 5 % significance. the evaluated variables were: height of plants, number of tillers per m2, grains per panicle, length of panicles, number of panicles m2, days to flowering, days to harvest, number of grains per panicle, weight of 1000 grains and yield per hectare . The results found in the present experimental work show that the application of chemical fertilizers plus organic fermentation is an alternative in the nutritional system of rice cultivation, since they maximize the production of grain. The highest yield of the crop (6197.53 kg / ha) was presented applying 69 kg / ha N - 46 kg / ha P - 90 kg / ha K plus Granumax 150 kg / ha.